2020
DOI: 10.1177/0020294020944955
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective numerical simulation of geometrical characteristics of laser cladding of cobalt-based alloy based on response surface methodology

Abstract: The objectives of this study are to optimize the key process parameters of laser cladding remanufacturing parts, improve the sealing quality of the hemispherical valve and prolong and improve its service life and reliability. A high-power fiber-coupled semiconductor laser was used to fabricate a single Co-based alloy cladding layer on the pump valve material ZG45 plate. The key process parameters of laser power, scanning speed and powder feeding rate in the process of laser remanufacturing are taken as optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The p values of AB, BC, A 2 , and C 2 were 0.10, 0.14, 0.94, and 0.22, respectively, which are nonsignificant influencing factors, so were removed from the table to ensure the accuracy of the model; in addition, in the expression of the bead height model, A, B, C, AC, and B 2 were found to be significant influencing factors, with p values of AB, BC, A 2 , and C 2 are 0.59, 0.41, 0.12, and 0.09, respectively, making them nonsignificant influencing factors. To ensure the accuracy of the model, these factors were also removed from the model [22]. Thus, the coded value regression equations with the surfacing speed, surfacing voltage, and surfacing current as the variables, and the bead height and the dilution rate as the response values were obtained, namely,…”
Section: Mathematical Model Establishment and Fitting Results Analysismentioning
confidence: 99%
“…The p values of AB, BC, A 2 , and C 2 were 0.10, 0.14, 0.94, and 0.22, respectively, which are nonsignificant influencing factors, so were removed from the table to ensure the accuracy of the model; in addition, in the expression of the bead height model, A, B, C, AC, and B 2 were found to be significant influencing factors, with p values of AB, BC, A 2 , and C 2 are 0.59, 0.41, 0.12, and 0.09, respectively, making them nonsignificant influencing factors. To ensure the accuracy of the model, these factors were also removed from the model [22]. Thus, the coded value regression equations with the surfacing speed, surfacing voltage, and surfacing current as the variables, and the bead height and the dilution rate as the response values were obtained, namely,…”
Section: Mathematical Model Establishment and Fitting Results Analysismentioning
confidence: 99%
“…Among them, the three process parameters of laser power, scanning speed, and powder feeding rate are more studied [81]. Cui et al [82] used the response surface methodology to optimize a cobaltbased alloy coating's process parameters. Their work laid the foundation for the setup of the laser cladding processing parameters for multi-track coatings made from cobalt.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…During the laser processing, the POM workpiece is placed on a high-precision motion platform, and the pulse laser with high repetition frequency and high energy density is applied to the surface of the workpiece using different laser processing parameters [26], which is radiated on the surface of the specimen according to the set scanning path and causes it to melt and vaporize [27], thus processing the elliptical texture with a certain depth. The ultrasonic cleaning device was used to clean the processed samples.…”
Section: Univariate Experimentsmentioning
confidence: 99%
“…They analysed the impact of process parameters on various response variables, and experimental results showed that the predictive model had good accuracy. Cui et al [26] established regression prediction models between process parameters and coating width, coating height, coating depth, aspect ratio and dilution rate. The average error between the predicted values of each regression prediction model and the experimentally measured values is less than 10 %.…”
Section: Introductionmentioning
confidence: 99%